2013
DOI: 10.1152/ajprenal.00613.2012
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 inhibits sodium reabsorption by ETAand ETBreceptors in the mouse cortical collecting duct

Abstract: The collecting duct (CD) is a major renal site for the hormonal regulation of Na homeostasis and is critical for systemic arterial blood pressure control. Our previous studies demonstrated that the endothelin-1 gene (edn1) is an early response gene to the action of aldosterone. Because aldosterone and endothelin-1 (ET-1) have opposing actions on Na reabsorption (JNa) in the kidney, we postulated that stimulation of ET-1 by aldosterone acts as a negative feedback mechanism, acting locally within the CD. Aldoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Interestingly, the IMCD is a major site for the production of endothelin-1 (ET-1) [44], which is capable of binding four G αq coupled GPCR isoforms ETA, ETB1, ETB2 and ETC. In the collecting duct, ET-1 binding to ETA or ETB decreases ENaC activity [45, 46]; however, it role in Cl − secretion has not been examined. Recently, glycogen synthase kinase 3β (GSK 3β), a kinase in the Wnt signaling pathway, was shown to stimulate cAMP production by activating adenylyl cyclase in collecting duct cells.…”
Section: Regulation Of Cl− Secretion By the Collecting Ductsmentioning
confidence: 99%
“…Interestingly, the IMCD is a major site for the production of endothelin-1 (ET-1) [44], which is capable of binding four G αq coupled GPCR isoforms ETA, ETB1, ETB2 and ETC. In the collecting duct, ET-1 binding to ETA or ETB decreases ENaC activity [45, 46]; however, it role in Cl − secretion has not been examined. Recently, glycogen synthase kinase 3β (GSK 3β), a kinase in the Wnt signaling pathway, was shown to stimulate cAMP production by activating adenylyl cyclase in collecting duct cells.…”
Section: Regulation Of Cl− Secretion By the Collecting Ductsmentioning
confidence: 99%
“…demonstrated that endothelin-1 decreases the activity of ENaC in isolated rat collecting ducts, through ETB, but not ETA receptors [162]. Endothelin-1 decreases sodium reabsorption in isolated mouse collecting ducts, through both ETA and ETB receptors [163]. The inhibition of ENaC by endothelin-1 is abolished by a selective Src kinase inhibitor, PP2 [164].…”
Section: Tgfβ1 and Endothelin-1mentioning
confidence: 99%
“…Furthermore, ETA blockade in intact rats reduces the natriuretic and diuretic response to renal medullary infusion of hyperosmotic saline (Boesen and Pollock, 2010). Finally, ET-1 inhibition of amiloride-sensitive transepithelial sodium flux in vitro microperfused mouse collecting duct is prevented by ETA antagonism (Lynch et al, 2013). Thus, collecting-duct ETA may well be capable of inhibiting sodium and water transport.…”
Section: Site Of Endothelin a Receptor Antagonist Fluid Retentionmentioning
confidence: 97%